A Model in Support of the Implementation of Enterprise Resource Planning (ERP) Projects by System Dynamics Approach - Mohammad Rahim Ramazanian; Reza Esmaeilpour; Marjan Hadidi Masouleh (Journal of Information Technology Management)
Recent studies have indicated that the rate of successful Enterprise Resource Planning (ERP) implementation projects is reduced and risk of implementation is increased to the same extent. Accordingly, this study provides a model in support of ERP implementation using system dynamics approach by behavioral simulation in the Vensim software environment. This study is an applied research and due to the nature, this is a descriptive and analytical research. For the purpose of research, proposed simulation model is used in Paksan organization in order to present policies for the improvement in the organization's ERP system implementation project by testing different strategies in simulation environment. Since in this research the improvement of ERP system implementation project has been considered in terms of time and cost, policies have been proposed to reduce these two factors that their results were this: increasing the number of experienced users, eliminating customization and increasing the amount of training cause improvement in project perfpemance.